2016
DOI: 10.1590/bjpt-rbf.2014.0154
|View full text |Cite
|
Sign up to set email alerts
|

The role of daily physical activity and nutritional status on bone turnover in cystic fibrosis: a cross-sectional study

Abstract: BackgroundNutritional status and daily physical activity (PA) may be an excellent tool for the maintenance of bone health in patients with cystic fibrosis (CF).ObjectiveTo evaluate the relationship between nutritional status, daily physical activity and bone turnover in cystic fibrosis patients.MethodA cross-sectional study of adolescent and adult patients diagnosed with clinically stable cystic fibrosis was conducted. Total body, femoral neck, and lumbar spine bone mineral density (BMD) were determined by dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Nixon et al [9] found no correlation between the reported time spent in vigorous activities and maximal oxygen uptake (V'O 2 peak) in 30 subjects aged 7-19 years. Schneidermann et al [5] found no significant association between V'O 2 peak and habitual PA. Controversially another author speculated that PA could be a significant, although relatively weak, predictor of V'O 2 peak in CF [8]. The positive relationship between PA levels and aerobic fitness is supported by a recent study by Savi et al [22].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Nixon et al [9] found no correlation between the reported time spent in vigorous activities and maximal oxygen uptake (V'O 2 peak) in 30 subjects aged 7-19 years. Schneidermann et al [5] found no significant association between V'O 2 peak and habitual PA. Controversially another author speculated that PA could be a significant, although relatively weak, predictor of V'O 2 peak in CF [8]. The positive relationship between PA levels and aerobic fitness is supported by a recent study by Savi et al [22].…”
Section: Discussionmentioning
confidence: 92%
“…A growing body of research has demonstrated that exercise training and physical activity (PA) are associated with decreased mortality [3], slower rate of decline in respiratory function [4,5], higher bone mineral density [6], improved nutritional status and health-related quality of life [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty‐one studies (33.1%) recruited adult patients aged between 18 and 57 years and a total number of 1983 patients with CF. Only 15 studies included patients older than 40 years . Ten studies (8.1%) included both children and adults (range: 4–66 years, N = 768).…”
Section: Resultsmentioning
confidence: 99%
“…DXA was used in 56 studies (33.9%, see Tables and for details), whereas 12 studies (9.7%) used only BIA; 5 studies (4%) applied SF, and 5 other studies used the total body potassium counting method (TBK) . Three studies used ultrasound (ULT), , 3 studies used peripheral quantitative computed tomography (pQCT), 1 study used air displacement plethysmography (ADP), and 1 study used MRI .…”
Section: Resultsmentioning
confidence: 99%